Does a global young consumer exist? A comparative study of South Korea and Poland - Agnieszka Kacprzak; Katarzyna Dziewanowska (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2015)
In this paper we analyse the phenomenon of the global young consumer. Taking the example of young people from South Korea and Poland, we show similarities and differences in their reaction to modern socio-cultural trends influencing consumption patterns. The globalization process is believed to affect most young people designated Generation Y. They were brought up in the Internet age, which ease homogenization of cultural values, attitudes and consumer behaviour. On the other hand, the impact of local culture on their behaviour as consumers must still be considered. The results of quantitative studies conducted among 200 young Korean and Polish consumers were investigated. A research tool, in the form of six indices measuring the attitudes towards modern socio-cultural trends influencing consumer behaviour, was used (materialism, impulsive consumption, greening, virtualization, virtual tribalism, tribalism in real space). The findings suggest that there are significant differences in the level of materialism, greening and tribalism in real space between young Poles and Koreans while their attitudes to behaviour connected to Internet usage are similar. Therefore, the assumption can be made that the widespread use of new technologies is a characteristic feature that bonds Generation Y on a global scale while other aspects of consumer behaviour remain strongly influenced by local cultures. This makes a significant contribution to knowledge of marketing strategy planning in global companies targeting young consumers. It seems that the ethnocentric approach can be implemented only in the new technologies sector while for other products and services the polycentric strategy is more appropriate.
Keywords: M30; M31; M39; M00; 650; globalization; young consumers; Generation Y; Korea; Poland; segmentation